Evaluasi pelaksanaan program rumah tunggu kelahiran (RTK) dengan logic model di Kabupaten Jayapura Provinsi Papua - Vera Iriani Abdullah; Wiwit Vitania (Universitas Jenderal Achmad Yani Yogyakarta, 2022)
Background: One of the government's efforts to increase the coverage of deliveries in health facilities is by establishing a maternity waiting home (MWH)Objective: This study aims to evaluate the implementation of the MWHs Program in the Depapre district and Unurum Guay, Jayapura district, Papua. The component of study including the input component, process, output and external factor Method: Type of this research is qualitative research, evaluate the program using the Logic model conducted in MWHs Jayapura district. The research subjects included 9 program managers, and 28 people in community.. Data collection performed with interviews, observation, questionnaires and document analysisResults: The results indicate that the input component includes the availability of funding, policies, facilities infrastructure, and inadequate transportation which has impact for MWHs service process. Process of implementation of MWHs in form of disseminating information, cooperation, recording, reporting and supervision has not optimal. The output component form of MWHs utilization already well even though in the following year there was a decrease Conclusion: The implementation of the MWHs program is not optimal. The input component is still inadequate, the process component has not run optimally and the output component has not achieved the expected results. Strategy is needed for program implementation runs a well